Factors Influencing Farmers' Decision to Participate in the RHL (Forest and Land Rehabilitation) Program in Lengkiti District, OKU Regency - Dina Oktavia; Munajat; Fifian Permata Sari; Anggi Fatmayati Manggi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This research aims to determine what factors influence farmers' decisions to participate in Forest and Land Rehabilitation activities in Lengkiti District, OKU Regency. This study employed a survey approach of research. In this work, logistic regression analysis was utilized to analyze the data. The findings revealed that the independent variables: number of family members, land area, and workdays, significantly affected coffee growers' decisions to participate in the Forest and Land Rehabilitation (RHL) program.